PENAMBAHAN DAGING IKAN LELE (Clarias Sp) TERHADAP KADAR PROTEIN DAN ORGANOLEPTIK CHIPS IKAN - nurul mukminah; Cindy Lestari; Maulina Agustiana (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Fish chips are a fortified snack made from the main ingredients of serelia and fish. The purpose of this study was to improve the nutritional value and recommend the best formulation of catfish (Clarias Sp) chips. Completed Randomized Design method was employed-using three different concentration of meat of catfish treatments: 10%, 20%, and 30% with three repetition. Parameters of experiment were crude protein and hedonic test. Parametric data was analyzed with ANOVA; to distinguish treatment, Duncan was employed; to test non-parametric data, Kruskal-Wallis test was employed. The results showed that the increase of catfish meat percentage had significant effect (P <0,01) on protein content. Organoleptic results of flavor and texture, fish chips with meat of catfish as much as 20% is the preferred formulation by panelists. The recommended formulation of fish meat in the manufacture of fish chips is 20%.